1993
DOI: 10.1007/bf00320981
|View full text |Cite
|
Sign up to set email alerts
|

Temperate rainforest lichens in New Zealand: high thallus water content can severely limit photosynthetic CO2 exchange

Abstract: CO exchange rate in relation to thallus water content (WC, % of dry weight) was determined for 22 species of lichens, mainly members of the genera Pseudocyphellaria and Sticta, from a temperate rainforest, Urewere National Park, New Zealand. All data were obtained in the field, either using a standard technique in which the lichens were initially wetted (soaked or sprayed, then shaken) and allowed to slowly dry, or from periodic measurements on samples that were continuously exposed in their natural habitat. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
88
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 28 publications
5
88
2
Order By: Relevance
“…The positive value means the respiration was stronger than photosynthesis, and the negative value means CO 2 assimilation occurred. As for cyanolichen, it was reported that net photosynthesis was severely depressed by both too low and too high water contents [25,27]. But a seemingly conflicting result was found in LSCs in the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…The positive value means the respiration was stronger than photosynthesis, and the negative value means CO 2 assimilation occurred. As for cyanolichen, it was reported that net photosynthesis was severely depressed by both too low and too high water contents [25,27]. But a seemingly conflicting result was found in LSCs in the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…It is significant that activation of PSII in the halite cyanobacteria did not occur until liquid water was produced through deliquescence (8) and/or water vapor condensed within the nanopores of halite (9). Hence, it seems that photosynthesis in cyanobacteria can only be activated in the presence of liquid water (50). All these factors can cause different viability states of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most lichens seem to have an optimal WC for photosynthesis, for net CO^ uptake may be depressed when the WC is too high (Lange et al, 1994). This depression has been shown to result from high COd iffusion resistance through a water-saturated fungal matrix (Cowan, Lange & Green, 1993), but the relati\-e inhibition of net photosynthesis at supraoptimal WC varies between species (Lange et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Most lichens seem to have an optimal WC for photosynthesis, for net CO^ uptake may be depressed when the WC is too high (Lange et al, 1994). This depression has been shown to result from high COd iffusion resistance through a water-saturated fungal matrix (Cowan, Lange & Green, 1993), but the relati\-e inhibition of net photosynthesis at supraoptimal WC varies between species (Lange et al, 1994). Several features of the lichens might explain these different responses, including variations in the gross morphology of the lichen thallus, production of water-repellent substances by some mycobionts and differences in the organization of the mycohiontphotobiont interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation